Munculnya Tingkah Laku Baru Para Pengguna Internet pada Masyarakat Desa Broadband - Asy Syifa Rakhmadevi; Karolina Lamtiur Dalimunthe; Retno Hanggarani Ninin; Noer Fauzi Rachman (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to describe a villager's behavior as a new internet user in a broadband village. Qualitative methods with ethnographic approaches were used, and the data was obtained based on the experience of living in Broadband Village for two months. This research was conducted in Mandalamemar Village, certified as Broadband Village by the Ministry of Communication and Information. Results have shown that internet emerging villagers new behavior from the individual, group and community levels. The new behavior consists such as; the emergence of awareness to find out new things from the internet, a new needs of tertiary things, internet addiction, a new way of online communication between groups, the rise of more people creating new groups and lastly, the public concern due to hoaxes spread through the internet.